Competency of Muslim Doctors - Mutmainnah; Algristian, Hafid; Azizah, Nur (Jurnal Medis Islam Internasional, 2022)
Background: In the medical profession, a doctor will often be faced with situations of uncertainty to make the right decisions and diagnoses. In this case, making a Muslimdoctor to be able to have a good impact on patients. A Muslim doctor is expected to be able to implement professional and reliable competencies in the future. In facing the future, with all the challenges in the medical world, ethical principles, moral values and good competence are needed in order to be able to provide the best health services by minimizing risks and side effects, and prioritizing greater benefits so as not to harm doctors as service providers, and patients as recipients of health services.Objective: This study aims to learn more about the definition and principles of medical ethics, muslim doctor competence, and Islamic medical moral values.Methods: The article source in the same field was compiled. Through a several literature search of reputable journals wich maximum published in the past 10 years.Result: Several article was found, and all the article said the moral values in Islamic medicine are closely related to the personality of Muslim Doctors.Conclusion: The guidelines for islamic medical ethics as muslim are Qur’an, Hadist, Ijma’ and Qiyas. The four main moral principles for be a good doctor are the principle of autonomy, beneficence, non-maleficence, and the principle of justice. The competence of Muslim doctors has a close relationship with ethical principles, moral values, and law. The moral values of muslim doctors includes self-awareness, such as awareness of fitrah (inne-rself) and social awareness as caliph (external-self-awareness).